High-performance liquid chromatography analysis of purine nucleosides in human gingival crevicular fluid - Jahngen, E.G.E.; Brecx, M.; Rossomando, E.F. (Archives of oral biology, 1984)
Samples of human crevicular fluid were collected and analysed by high-performance liquid chromatography (HPLC) for purine nucleotides, nucleosides and bases. The complex chromatograms, had concentrations of compounds in two regions. Region (I) corresponded to purine bases and nucleosides, adenine and hypoxanthine were specifically identified. In region (II), where purine nucleotide mono- and diphosphates are generally observed, IMP and AMP were identified. In one subject with advanced periodontitis, additional compounds in region II were observed; crevicular fluid in gingivitis had the majority of their purine-containing compounds in region I.